White light from annealed porous silicon: Broadband emission from violet to the near infrared - Marín Ramírez, Oscar Alonso (2015)
We report white light emission under UV excitation from porous silicon (PS) samples annealed at different temperatures and surrounding atmospheres. The photoluminescence (PL) spectra show a broad emission from ultraviolet to near infrared. Annealed PS samples were studied by photoluminescence, FTIR and EPR spectroscopies. The PL spectra were found to include three main components centered at the violet, green and infrared. The FTIR experiments suggest the formation of a system composed by silicon nanocrystals embedded in a nonstoichiometric silicon oxide matrix (nc-Si/SiOx). The EPR measurements reveal the existence of the well-know Pb0 (g~2.007) and Pb1 (g~2.004) centres, and of a signal at g~1.9997. The combined PL, FTIR and EPR results suggest that violet and green emissions come from oxygen-excess defects in SiOx while the infrared emission is related to defects located at Si/SiOx interfaces.